Flexural modelling and finite element analysis of frc beams reinforced with PVA and basalt fibres and their validation - Ayub, T. (Hindawi Limited, 2018)
A flexural capacity model for fibre-reinforced concrete (FRC) beams reinforced with PVA and basalt fibres is suggested for the rectangular beam sections. The proposed models are based on the concept of equivalent stress block parameters for both compressive and tensile stresses, similar to Eurocode and ACI code. The parameters are defined by allowing the conversion of the stress-strain models into equivalent rectangular stress blocks, similar to Eurocode 2. The flexural model is suggested to determine the loading capacity of 21 FRC beams containing up to 3 volume fraction of PVA and basalt fibres without reinforcing bars. In order to investigate the accuracy of the proposed flexure models, finite element analysis (FEA) of the same beams was carried out using the compressive and tensile stress-strain curves. Furthermore, 21 FRC beams subjected to three-point bending were tested. The results of the flexural models showed good agreement with the load-carrying capacity of the tested FRC beams, and the results of FEA of all beams showed a good correlation with the experimental results in terms of the maximum load, load versus midspan deflection patterns, and the maximum tensile strains. Â© 2018 Tehmina Ayub et al.